High-intensity cardiorespiratory and strength exercises reduced emotional distress and fatigue in patients with axial spondyloarthritis: a randomized controlled pilot study. (4th March 2018) - Sveaas, SH; Berg, IJ; Fongen, C; Provan, SA; Dagfinrud, H
Abstract : Objective : To investigate the effect of high-intensity exercise on emotional distress, fatigue, and ability to do a full day's activities in patients with axial spondyloarthritis (axSpA). Method : A total of 28 physically inactive axSpA patients were randomized to either an exercise group (EG), which performed 12 weeks of cardiorespiratory and strength exercises, or a control group (CG), which received treatment as usual. The outcomes reported in this paper are secondary outcomes in the trial and included emotional distress (General Health Questionnaire-12, 0–36, 36 = worst), fatigue [numeric rating scale (NRS), 0–10, 10 = worst], and ability to do a full day's activities (NRS, 0–10, 10 = worst). Post-intervention differences were assessed by analysis of covariance with baseline values as covariates. Results : Twenty-four patients were included in the analyses. All patients in the EG followed the exercise protocol. The EG had a statistically significant beneficial effect [mean group differences (95% confidence interval)] on emotional distress [−5.8, (−9.7, −1.9), p < 0.01], fatigue [−2.4, (−4.3, −0.4), p = 0.02], and ability to do a full day's work [−2.2, (−3.9, −0.4), p = 0.02] compared to the CG. Conclusion : This pilot study showed promising effects of cardiorespiratory and strength exercises on emotional distress, fatigue, and ability to do a full day's activities in patients with axSpA. The findings need to be confirmed in a larger trial.